Containing spectacle in the transnational public sphere. Issue 6 (1st November 2016) - Lester, Libby
ABSTRACT: This paper analyzes the discursive struggle over the reach and containment of spectacle in environmental politics to provide (a) case study-based evidence of how, on one hand, transnationally shared environmental awareness and concern, emerging in part through spectacle, is translating into expectations of participation and demands for accountability, and (b) how this is already impacting the ways in which environmental politics is being understood and enacted locally, regionally and transnationally. Drawing on recent mediated debate over the Great Barrier Reef, it finds that while the transnational is clearly an ambition for environmental campaigners, and the perception that transnational publics are emerging is already impacting environmental politics, the potency of these publics and their capacity to meaningfully negotiate accountability is yet to be empirically confirmed. Nevertheless, measures to contain spectacle are providing a potency for a transnational public sphere, even if in reality it is still little more than a specter.